Breeding and Engineering Trees to Accumulate High Levels of Terpene Metabolites for Plant Defense and Renewable Chemicals - Peter, Gary F. (Frontiers in Plant Science, 2018)
Plants evolved the capacity to synthesize highly diverse sets of secondary metabolites which are important for plant adaptation and health. In forest trees, many classes of compounds, particularly ones related to defense against insects, fungi and bacteria accumulate to levels that enable their recovery and commercial use. One of the oldest examples is conifer terpenes, but terpenes are important secondary products from other tree species including eucalypts. Because terpenes, latex and natural gums are synthesized and stored in specialized secretory glands, ducts, and laticifers in mostly pure forms they can be collected from live trees in addition to being extracted during industrial processing of wood. This minireview describes the potential of breeding and genetic engineering approaches to increase the quantities of terpene secondary metabolites to increase the amount of secondary products and thereby increasing the value of planted and managed forest trees. I advance the view that breeding and genetic engineering of metabolic pathways and specialized cell secretory structures can dramatically increase tissue terpene content.